Exploring Cyber Fandom On Westlife Comeback Twenty Four - Iin Rachmawati (Jurnal Ilmu Komunikasi, 2020)
Fandom had found anywhere in the world. What makes this research is different from others that the 1990s boy band Westlife has proved that even after 20 years of career and decided to comeback in 2019, their fans has still been excited on watching their shows. Due to that reason, the researcher is interested in digging more about how fandom and cyber fandom work through Westlife’s twenty tour 2019 as well as about the fandom context of Westlifers. In general, this research will use qualitative descriptive method by using purposive sampling technique. The result shows that the role of fandom and cyber fandom ‘Westlife Indonesia’ is quite important towards all Westlifers because this fan base provided everything they need to get closer to their idols and other fans. Also, there are four basic fandom contexts appeared in Westlifers: (1) virtual communication, (2) creativity, (3) knowledge or information, and (4) civil strength or organization.